Growth and Morpho-Stomatal Response of Kenaf (Hibiscus cannabinus) to Varying Water, Light, and Soil Conditions - Jonathan Ogayon Hernandez; Leah Grace Abalos Manese; Hazelyn Lacasa Lalog; Vrenissa Jane Valenzuela Herradura; Willie Payawan Abasolo; Lerma San Jose Maldia (Department of Forestry, Faculty of Agriculture, University of Lampung, 2023)
This study investigated the stomatal responses of kenaf (Hibiscus cannabinus) to varying water, light, and soil conditions to explain how the species acclimatize to the changes in growing conditions. Seedlings were subjected to different watering regimes (daily – CON, 2 days interval – W2, 3 days interval – W3), light intensities (high, moderate, low), and soil conditions (garden soil – GS, Mt Makiling soil – MAK, UP Land Grant soil – UPL). The biomass, stomatal density (SD), epidermal cell density (ECD), stomatal index (SI), stomatal aperture length (SAL), guard cell length (GCL), stomatal area (SA), and potential conductance index (PCI) were measured across treatments. Water and light treatments had significant effects, but soil treatment did not affect most of the parameters measured. CON and/or W2 and high light intensity resulted in a higher SD, SI, SAL, and GCL, which resulted in a higher PCI, compared with the other water and light treatments. Contrarily, W3-treated seedlings had lower SD but significantly lower SAL, GCL, PCI, and aboveground biomass, compared to CON and W2-treated ones. Biomass allocation to root was also significantly higher in W3-treated seedlings. Therefore, kenaf seedlings exhibited a degree of stomatal plasticity in response to contrasting water, light, and soil conditions. Keywords: biomass allocation, potential conductance index, shade tolerance, stomatal index, water stress